Pencegahan penularan infeksi Human Immunodeficiency Virus (HIV) dari ibu ke anak di Indonesia: sebuah tinjauan pustaka - Komang Ayu Witarini (DiscoverSys Inc., 2021)
Human Immunodeficiency Virus (HIV) can be transmitted from an HIV-positive woman to her child during pregnancy, childbirth, and breastfeeding. Mother-to-child transmission (MTCT), also known as ‘vertical transmission’, accounts for the vast majority of infection in children (0-14 years). Prevention of mother-to-child HIV infection transmission (PMTCT) programs offers a range of services for women of reproductive age (15-49 years) living with or at risk of HIV to maintain their health and stop their infants from acquiring HIV. WHO promotes a comprehensive approach to PMTCT programs which include: preventing new HIV infections among women of reproductive age, preventing unintended pregnancies among women living with HIV, preventing HIV transmission from women living with HIV to her baby, and providing appropriate treatment, care, and support to mothers living with HIV, their children, and families. The health service program to prevent HIV transmission from HIV-infected pregnant women to their babies includes the following activities: integrated ANC services, including offering and testing HIV to pregnant women; HIV diagnosis in pregnant women; administering antiretroviral therapy to pregnant women; safe delivery; arrange for subsequent pregnancies; management of feeding for infants and children; administration of Antiretroviral (ARV) prophylaxis and cotrimoxazole in children; HIV diagnostic testing in children; and immunization. The risk of MTCT of HIV can be reduced to less than 2% with optimal PMTCT programs. Human Immunodeficiency Virus (HIV) dapat ditularkan dari ibu yang terinfeksi kepada bayi yang dikandung selama kehamilan, persalinan dan menyusui. Penularan infeksi HIV dari ibu kepada bayi yang dikandung, dikenal dengan istilah transmisi vertikal, merupakan cara penularan infeksi tersering dijumpai pada anak usia 0-14 tahun. Program pencegahan penularan infeksi HIV dari ibu ke anak (PPIA) merupakan upaya terhadap perempuan usia produktif (15-49 tahun) yang terinfeksi atau memiliki risiko terinfeksi HIV untuk tetap terjaga kesehatannya, serta mencegah menularkan infeksi HIV kepada bayi yang dikandung. World Health Organization (WHO) mempromosikan upaya komprehensif dari PPIA, terdiri dari: mencegah terjadinya penularan HIV pada perempuan usia reproduksi, mencegah kehamilan yang tidak direncanakan pada perempuan dengan HIV, mencegah terjadinya penularan HIV dari ibu hamil HIV positif ke bayi yang dikandungnya, serta memberikan dukungan psikologis, sosial, dan perawatan kesehatan kepada ibu HIV positif beserta bayi dan keluarganya. Program pelayanan kesehatan untuk mencegah penularan HIV dari ibu hamil terinfeksi HIV kepada bayi yang dikandung mencakup kegiatan sebagai berikut: layanan antenatal care (ANC) terpadu termasuk penawaran dan tes HIV pada ibu hamil; diagnosis HIV pada ibu hamil; pemberian terapi antiretroviral pada ibu hamil; persalinan yang aman; menunda dan mengatur kehamilan berikutnya; tatalaksana pemberian makanan bagi bayi dan anak; pemberian profilaksis Antiretroviral (ARV) dan kotrimoksazol pada anak; pemeriksaan diagnostik HIV pada anak; serta imunisasi. Dengan upaya PPIA yang optimal, risiko penularan HIV dari ibu ke anak dapat diturunkan sampai kurang dari 2%.